The Influence of Marketing Mix on Consumer Loyalty Through Consumer Satisfaction at the Pusat Grosir Sepatu (PGS) in Mojokerto City - Mei, Nanang Andhiyan Mergining; Kridaningsih, Anna; Andhiyan, Alferiano Putra; Agmadamara, Divela Zulvianasya Gadis (SENTRI: Jurnal Riset Ilmiah, 2025)
Retail business competition in the footwear sector is driven by increased footwear sales. The role of the local government in this regard is the Mojokerto City government providing facilities the Pusat Grosir Sepatu (PGS). Pusat Grosir Sepatu (PGS) in Mojokerto City was established in 2023. Over time, sales at the Pusat Grosir Sepatu (PGS) in Mojokerto City have fluctuated. In response to this, various efforts have been made, including adding variety and improving product quality, improving facilities, enhancing personal selling skills, providing special prices, promoting on social media, and other efforts. These efforts are part of the marketing mix. These improvements are aimed at increasing customer satisfaction and thus fostering customer loyalty at the Pusat Grosir Sepatu (PGS) in Mojokerto City. Based on this explanation, this study aims to test and prove the effect of the marketing mix on customer loyalty through customer satisfaction at Pusat Grosir Sepatu (PGS) in Mojokerto City. There are 3 variables, namely the marketing mix variable with 7 mixes, consumer satisfaction, and consumer loyalty. Data processing used SmartPLS 4.1. The results of the hypothesis test obtained the results that there is an influence of the marketing mix on consumer satisfaction as evidenced by P values of 0.000 < 0.05. The influence of the marketing mix on consumer loyalty is evidenced by P values of 0.000 < 0.05. The influence of consumer satisfaction on consumer loyalty is evidenced by P values of 0.00 < 0.05. The influence of service quality on consumer loyalty through consumer satisfaction is known to be P values of 0.001 < 0.05. From the adjusted R square value, it is known that the influence of the marketing mix on consumer satisfaction is 58% and the influence of the marketing mix and satisfaction on consumer loyalty is 59.7%.